Corporate Responsibility towards the Protection and Management of the Environmental Land of Used Mine - Mahfud Mahfud (Administrative and Environmental Law Review, 2021)
Humans exploiting their natural resources must always be based on an environmental approach. This is reasonable because environmental problems are closely related to population growth, the impact of which is the high demand for natural resources. One of the natural resources most widely used by humans for various purposes is coal. The negative impact of coal mining is to trigger deforestation and exacerbate climate change. This writing uses normative juridical research. The approach used is the statutory approach. Therefore, the management process of exploring and exploiting every mining material, especially coal, requires various AMDAL mechanisms as part of environmentally sound development management. Provisions regarding mineral and coal mining activities oblige mining companies to carry out reclamation and post-mining activities of the mining areas they cultivate. The scope of the implementation of reclamation activities starts from exploration, land clearing, excavation of top and over-borders, coal excavation, land arrangement, revegetation, including nursery preparation, and maintenance and evaluation of activity results. Reclamation is carried out no later than one month after there are no more mining business activities on disturbed land. Reclamation and post-mining activities are one of the obligations of mining business activities.